2019
DOI: 10.3389/fcell.2019.00214
|View full text |Cite
|
Sign up to set email alerts
|

NKAP Regulates Senescence and Cell Death Pathways in Hematopoietic Progenitors

Abstract: NKAP is a multi-functional nuclear protein that has been shown to be essential for hematopoiesis. Deletion of NKAP in hematopoietic stem cells (HSCs) was previously found to result in rapid lethality and hematopoietic failure. NKAP deficient cells also exhibited diminished proliferation and increased expression of the cyclin dependent kinase inhibitors (CDKIs) p19 Ink4d and p21 Cip1. To determine how dysregulation of CDKI expression contributes to the effects of NKAP deficiency, NKAP was deleted in mice also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Using the CWPA, NKAP was successfully identified as the antigen of mAb TRA98, which specifically recognized germ cells. NKAP plays an important role in cell differentiation by affecting gene expression (Pajerowski et al., 2009; Shapiro et al., 2019). These findings may greatly contribute to research into the development and differentiation of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using the CWPA, NKAP was successfully identified as the antigen of mAb TRA98, which specifically recognized germ cells. NKAP plays an important role in cell differentiation by affecting gene expression (Pajerowski et al., 2009; Shapiro et al., 2019). These findings may greatly contribute to research into the development and differentiation of germ cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these previous studies, we postulated that GRAS1 lncRNA plays a protective role against cell death in multiple cancer cell types through a common mechanism. NF-κB activating protein (NKAP) is a multifunctional protein which promotes growth and development in highly proliferative human cells (Pajerowski et al 2009, Shapiro et al 2019, Okuda et al 2015. NKAP was first identified in yeast (Chen et al 2003) and has since been characterized as an RNA-binding protein in humans (Burgute et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB activating protein (NKAP) is a multifunctional protein which promotes growth and development in highly proliferative human cells (Pajerowski et al 2009, Shapiro et al 2019, Okuda et al 2015). NKAP was first identified in yeast (Chen et al 2003) and has since been characterized as an RNA-binding protein in humans (Burgute et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…NKAP functions as an oncogene and participates in the progression of cancer, including gastric cancer [25], colon cancer [26], and renal cell carcinoma [27]. In recent years, research groups from Mayo Clinic and the University of Pennsylvania reported that NKAP played a vital role in immune cell maturation and maintenance [28][29][30][31][32][33]. They found that deletion of NKAP in Treg cells and hematopoietic stem cells leads to cell death [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research groups from Mayo Clinic and the University of Pennsylvania reported that NKAP played a vital role in immune cell maturation and maintenance [28][29][30][31][32][33]. They found that deletion of NKAP in Treg cells and hematopoietic stem cells leads to cell death [28][29][30]. An interesting aspect that attracted us most was that NKAP knockdown induced increased lipid peroxidation in naive T cells [31] and a higher death rate in colon cancer cells [26]; these findings were similar to some of our research results on glioblastoma.…”
Section: Introductionmentioning
confidence: 99%